I still cannot get this problem and not sure if I am close, got it right or way off.....Can someone help?
I will show you my work thus far.....
Problem: x-1 4 1
----- + --------- = -------
x+3 xSquared +5x+6 x+2
Solving it as: x-1 4 1
----- ------- = -----
x+3 (x+3)(x+2) x+2
3 1
---------------------- = -------
2x+5x+3+6 x+2
7x+9 1
-------- = --------
x+2
7x+9 = x+2
7x+9-2 = x+2-2
7x-7 = x
7x = 7
x=1
I will show you my work thus far.....
Problem: x-1 4 1
----- + --------- = -------
x+3 xSquared +5x+6 x+2
Solving it as: x-1 4 1
----- ------- = -----
x+3 (x+3)(x+2) x+2
3 1
---------------------- = -------
2x+5x+3+6 x+2
7x+9 1
-------- = --------
x+2
7x+9 = x+2
7x+9-2 = x+2-2
7x-7 = x
7x = 7
x=1